Cultural Memory, Ventriloquism, and Performance: Reflections on Yasukuni Shrine - Matsubara, Masaki (Acta Orientalia Vilnensia, 2006)
Cornell UniversityThis article is a study of cultural memory, focusing on the case of a particular constructed memorial site, Yasukuni Shintō Shrine (hereafter, Yasukuni), one of the more controversial religious and political sites in Japan. By “cultural memory,” I mean a culturally constructed memory in light of needs and agendas of the present. It denotes exclusively constructions of the past as they are held by people in the given social, cultural, and historical context of the present. I argue that cultural memory is the memory through which people in the present use the past to drive an agenda in the present. This cultural memory is manifested by rituals or performances on special occasions such as commemoration days. What demands attention is that cultural memory is not about revealing past events as accurately as possible, neither is it necessarily about preserving cultural continuity. Rather it is about making “meaningful,” “persuasive,” “true” statements about the past in the particular given context of the present. Within this conceptual framework of cultural memory, this article demonstrates how the cultural memory of Yasukuni has actively constructed the past depending on certain social and cultural milieus of the present.